On the status of Trimeresurus monticola meridionalis Bourret, 1935 (Squamata: Viperidae) - David, Patrick; Vogel, Gernot (Zootaxa, 2012)
The name-bearing type specimens of Trimeresurus monticola meridionalis Bourret, 1935 are shown to be composed oftwo primary syntypes that are referable to Ovophis monticola (Günther, 1864) as currently conceived, and a secondarysyntype that belongs to Ovophis convictus (Stoliczka, 1870). Based on comparison of the three syntypes with other taxaof the Ovophis monticola-complex, historical analysis and a taxonomic review, we select one of the primary syntypes fromnorthwestern Vietnam as the lectotype of T. monticola meridionalis Bourret, 1935 and fix the status of this taxon as ajunior subjective synonym of Ovophis monticola. This position differs from the current synonymy of T. monticola meridionalis Bourret, 1935 with O. convictus.